Social impact measurement in social housing: a theory-based investigation into the context, mechanisms and outcomes of implementation. Issue 3 (16th June 2021) - Jones, Alice; Valero-Silva, Néstor
Abstract : Purpose: English social housing providers are increasingly turning to social impact measurement to assess their social value. This paper aims to understand the contextual factors causing this rise in the practice, specifically within this sector; the mechanisms that enable it to be effectively implemented within an individual organisation and the outcomes of successful implementation for individual organisations and more widely across the sector and beyond. Design/methodology/approach: A realist theory-based approach is applied to the study of a small number of social housing organisations and leaders within the sector to explore the use of social impact measurement. The paper addresses three questions: Why is social impact measurement being adopted in this sector? How is it successfully implemented? And what happens (outcomes) when it is successfully implemented? Addressing these questions necessitates deeper insight into the contextual pressures that have brought to the fore social impact measurement within the sector and the beneficial outcomes the practice provides (or is anticipated to provide) to social housing providers. The methodological approach of Realist Evaluation (Pawson and Tilley, 1997, 2004) is used to structure and analyse the empirical data and findings into a programme theory for social impact measurement. Realist Evaluation provides a programme theory perspective, seeking to answer the question "what works, for whom and in what circumstances?". In this research, the "whom" refers to English social housing providers and the circumstances are the contextual conditions experienced by the sector over the past decade. The programme theory aims to set out the links between the contextual drivers for social impact measurement, the mechanisms that bring about its implementation and the outcomes that occur as a result. Within this, greater detail on the implementation perspective is provided by developing an implementation theory using a Theory of Change approach (Connell et al., 1995; Fulbright-Anderson et al., 1998). The implementation theory is then embedded within the wider programme theory so as to bring the two elements together, thereby creating a refinement of the overall theory for social impact measurement. In turn, this paper demonstrates its importance (the outcomes that it can achieve for organisations and the sector) and how it can effectively be implemented to bring about those outcomes. Findings: Social housing providers use social impact measurement both internally, to determine their organisational priorities and externally, to demonstrate their value to local and national governments and cross-sector partners then to shape and influence resource allocation. The practice itself is shown to be an open and active programme, rather than a fixed calculative practice. Research limitations/implications: The intensive nature of the research means that only a limited number of cases were explored. Further research could test theories developed here against evidence collected from a wider range of cases, e.g. other types of providers or non-adopters. Practical implications: The research makes a strong contribution to practice in the form of a re-conceptualisation of how social impact measurement can be shown to be effective, based on a deeper understanding of causal mechanisms, how they interact and the outcomes that result. This is of value to the sector as such information could help other organisations both to understand the value of social impact measurement and to provide practical guidance on how to implement it effectively. Social implications: As the practice of impact measurement continues to develop, practitioners will need to be aware of any changes to these contextual factors and consider questions such as: is the context still supportive of impact measurement? Does the practice need to be adjusted to meet the needs of the current context? For instance, the recent tragedy at Grenfell Tower has led to a reconsideration of the role of social housing; a new Green Paper is currently being drafted (Ministry for Housing, Communities and Local Government, 2018). This may have a number of implications for social impact measurement, such as a rebalancing of emphasis on outcomes relating to environmental improvements, towards outcomes relating to the well-being of tenants. Originality/value: Existing literature is largely limited to technical guides. This paper links theory-based evaluation to practice contributing to social housing practice.